Does University-Industry engagement assist women in generating business income in emerging economies? Evidence from Malaysia - Eni Murdiati; Jawazi Jawazi; Nor Balkish Zakaria; Kazi Musa (Economies, 2023)
Women have a significant role in economic development in emerging economies like Malaysia through employment and business ownership. This is crucial for the family's survival and the prosperity of local economies-especially during an economic crisis or turmoil. Even though SMEs contribute to the local economy, their long-term viability is always uncertain. On the other hand, universities are considered indispensable and requisite contributors to the survival of this SME. This study, hence, evaluates the performance of women-owned small and medium businesses in conjunction with university-industry collaboration. Based on stratified sampling, a questionnaire survey was undertaken among regional SME female owners from various industries closely located to university campuses across different states post-pandemic in June 2021. The 227 female-owned SME responses showed a strong correlation between the university's contribution to SMEs' revenue. The findings demonstrate the importance of university support in marketing and training to SMEs' revenue according to women business owners. These findings accentuate the need for institutional policymakers to generate more profound knowledge and the need to keep ancillary longitudinal initiatives for sustainable business performance, especially among women, via university-industry arrangements.
Keywords: 330; women business; income sustainability; small medium enterprise (SME); university-industry engagement